Clinical characteristics of four cancer patients with SARS-CoV-2 infection in Wuhan, China - Shi-Hui Song; Tie-Long Chen; Li-Ping Deng; Yong-Xi Zhang; Ping-Zheng Mo; Shi-Cheng Gao; Wen-Jia Hu; Yong Xiong; Zhi-Yong Ma (BMC, 2020)
Abstract Background The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) led to the outbreak of pneumonia in Wuhan. The virus is highly infectious. Patients with cancer might be susceptible to the viral infection because of the immunosuppressive state cause by therapies on tumors. Case presentation We present the clinical features of four cancer patients who were infected with SARS-CoV-2 in late January of 2020 in our hospital. Cases 1 and 3 were diagnosed as mild and common type of coronavirus disease 2019 (COVID-2019) and survived from the viral infection. They acquired SARS-CoV-2 infection during their staying in hospital under radiotherapy and surgery of the tumors. Cases 2 and 4 suffered from severe type of COVID-19, and Case 2 was dead owning to the advanced age, uncontrolled chronic B cell lymphocytic leukemia and many other underlying diseases. The immunosuppressive state induced by liver transplantation and anti-rejection therapy might contribute to the severity of COVID-19 in Case 4, who suffered from hepatitis B related hepatocellular carcinoma. However, Case 4 was recovered from COVID-19 after a combination therapy against virus, bacteria and fungi, and also respiratory support. Nearly all patients showed a decrease in lymphocytes including total CD3+ T cells, B cells, and natural killer cells after infection of the virus. Conclusions The severity of COVID-19 might be influenced by immune system state and underlying diseases in cancer patients. And the treatment of SARS-CoV-2 infection in cancer patients is challenged by the immunosuppressive state of these patients under chemotherapy or surgery.